Naturalizing Callicott - Rolston, Holmes, 1932-2025, author; State University of New York Press, publisher (Colorado State University. Libraries, 2002)
In environmental philosophy, J. Baird Callicott is a doubtful guide; indeed he has gotten himself lost. He cannot find values in nature, not intrinsically. Indeed, at times he cannot find nature at all, only a nature commingled with culture. So, paradoxically, we need to get Callicott, though he thinks of himself as a naturalist, really naturalized. I cannot follow him in his arguments (1) about nature and culture, (2) about intrinsic natural value, and (3) about wilderness. He so resolutely opposes dichotomizing humans and nature that he cannot find any integrity for nature on its own. He remains, for a would-be naturalist, surprisingly humanistic--with people projecting their values onto nature, with people managing their landscapes. This is half the truth. But it is not the whole truth.
Keywords: naturalism; Callicott, J. Baird; anthropogenic value; value in nature; nature and culture; natural values; projected values; wilderness